Format guidelines to make them vivid, intuitive, and visual: Use simple formatting rules to optimize usability and accessibility of clinical practice guidelines. Issue 2 (June 2015) - Versloot, Judith; Grudniewicz, Agnes; Chatterjee, Ananda; Hayden, Leigh; Kastner, Monika; Bhattacharyya, Onil
ABSTRACT: Aim: We present simple formatting rules derived from an extensive literature review that can improve the format of clinical practice guidelines (CPGs), and potentially increase the likelihood of being used. Methods: We recently conducted a review of the literature from medicine, psychology, design, and human factors engineering on characteristics of guidelines that are associated with their use in practice, covering both the creation and communication of content. The formatting rules described in this article are derived from that review. Results: The formatting rules are grouped into three categories that can be easily applied to CPGs: first, Vivid: make it stand out; second, Intuitive: match it to the audience's expectations, and third, Visual: use alternatives to text. We highlight rules supported by our broad literature review and provide specific 'how to' recommendations for individuals and groups developing evidence-based materials for clinicians. Conclusion: The way text documents are formatted influences their accessibility and usability. Optimizing the formatting of CPGs is a relatively inexpensive intervention and can be used to facilitate the dissemination of evidence in healthcare. Applying simple formatting principles to make documents more vivid, intuitive, and visual is a practical approach that has the potential to influence the usability of guidelines and to influence the extent to which guidelines are read, remembered, and used in practice.